Model Doskonałości EFQM jako narzędzie wspomagające proces doskonalenia organizacji - Szydełko, Magdalena (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostępne wyłącznie w języku angielskim: The article presents The EFQM Excellence Model as a framework for managing and continuous improvement in the organization. The EFQM Excellence Model is a practical tool that can be used in a number of different ways: as a tool for self-assessment, a way to benchmark with other organizations, as a guide to identify areas for improvement, as the basis for a common vocabulary and a way of thinking and as a structure for the organization’s management system.